The Impact of Digital Village Construction on County-Level Economic Growth and Its Driving Mechanisms: Evidence from China - Pingping Wang; Chaozhu Li; Chenghao Huang (Agriculture, 2023)
Digital village construction is the key to future rural development in China. This study has empirically examined the impact of digital village construction on county-level economic growth in China, utilizing non-balanced panel data from 16 provinces and 622 counties for the years from 2018 to 2021. The study also investigated the underlying mechanisms and conducted heterogeneity and robustness tests using various analytical methods, including instrumental variables and the difference-in-differences (DID) approach. The findings reveal that digital village construction significantly enhances county-level economic growth, with a more pronounced effect observed in southern regions, eastern regions, and non-agricultural counties. The primary mechanism through which digital village construction drives economic growth at the county level is by promoting entrepreneurship. This study not only points out the key to digital village construction in China, but also enriches the theoretical research on digital village construction for economic growth. However, due to data limitations and the short time span of digital village construction, the results of the study are correct only for the period 2018–2021 in China. As digital village construction continues to progress, its impact on economic growth is likely to be even greater.